Research on the possibility of doing business activities in the markets - O. A. Zemlyanskiy (Вестник университета, 2022)
Companies of all types of organization and forms of ownership use different ways of doing business, have different opportunities and conditions for doing business. However, in order to achieve the effectiveness of such activities, to compare the capabilities of companies in different markets, it is possible to form a system of actions that is common and optimal for all types and forms of entrepreneurial activity. These activities are interconnected and include setting goals, determining the nature and direction of entrepreneurial activity in the markets and the formation of a structure for conducting and analyzing entrepreneurial activity, which allows achieving the set goals. The article proposes a generalized structure for conducting and analyzing the effectiveness of a company’s business for any type of business, including an analysis of external conditions, its impact on the implementation of its own, internal business opportunities in the market and the achievement of company goals in current and forecast market conditions. The structure will allow to explore and compare the possibility of effective business activities of companies of any form of ownership and types of activities in various markets.